2020
DOI: 10.3389/fvets.2020.598117
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of Ovulation and Presence of the Embryo Do Not Affect Uterine Horn Blood Flow During the First Month of Gestation in Llamas

Abstract: We determined if laterality of ovulation and intrauterine embryo location differentially induces changes in the mesometrial/endometrial vascularization area (MEVA) between uterine horns, during and after embryo migration, elongation and implantation in llamas. Adult, non-pregnant and non-lactating llamas (n = 30) were subjected to daily B-mode ultrasound scanning of their ovaries. Llamas with a growing follicle ≥8 mm in diameter in the left (n = 15) or right (n = 15) ovary were assigned to a single mating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Among Artiodactyla, some examples of laterality in implantation and gestation (Fernandez‐Baca et al, 1970; Sumar & Adams, 2007) have been already reported, regardless of laterality of ovulation (Fernandez‐Baca et al, 1970; Sumar & Leiva, 1979); this is the case of llamas ( Lama glama ) and alpacas ( Vicugna pacos ), where implantation and gestation exclusively occur in the left uterine horn (Ratto et al, 2020). Females from both species have a bicornate uterus that exhibits a clear asymmetry between uterine horns, with the left horn being larger and irrigated by a greater blood flow than its right counterpart (Del Campo et al, 1996, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Among Artiodactyla, some examples of laterality in implantation and gestation (Fernandez‐Baca et al, 1970; Sumar & Adams, 2007) have been already reported, regardless of laterality of ovulation (Fernandez‐Baca et al, 1970; Sumar & Leiva, 1979); this is the case of llamas ( Lama glama ) and alpacas ( Vicugna pacos ), where implantation and gestation exclusively occur in the left uterine horn (Ratto et al, 2020). Females from both species have a bicornate uterus that exhibits a clear asymmetry between uterine horns, with the left horn being larger and irrigated by a greater blood flow than its right counterpart (Del Campo et al, 1996, 2009).…”
Section: Discussionmentioning
confidence: 99%